2010
DOI: 10.1016/j.heares.2010.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Responses of the ear to low frequency sounds, infrasound and wind turbines

Abstract: Infrasonic sounds are generated internally in the body (by respiration, heartbeat, coughing, etc) and by external sources, such as air conditioning systems, inside vehicles, some industrial processes and, now becoming increasingly prevalent, wind turbines. It is widely assumed that infrasound presented at an amplitude below what is audible has no influence on the ear. In this review, we consider possible ways that low frequency sounds, at levels that may or may not be heard, could influence the function of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
129
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(133 citation statements)
references
References 85 publications
(109 reference statements)
2
129
1
1
Order By: Relevance
“…Although three of the studies [6][7]24] suggested that low-frequency sound energy wind turbines (i.e., infrasound below 20 Hz) may directly and negatively affect health, the level of evidence for these studies is also weak (expert opinions [7,24] and a review [6] citing these two studies).…”
Section: Summary Of Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Although three of the studies [6][7]24] suggested that low-frequency sound energy wind turbines (i.e., infrasound below 20 Hz) may directly and negatively affect health, the level of evidence for these studies is also weak (expert opinions [7,24] and a review [6] citing these two studies).…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Complaints resulting from the proximity to wind turbines vary in their nature, and distress is often attributed to different mechanisms, such as noise, visual impact, sleep disturbance, infrasound, and others [5][6][7]. Noise is the complaint that has been studied most often, especially given that environmental noise has become one of the major public health concerns of the 21st century [8].…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Low frequency noise is generated by many everyday sources such as household appliances, transportation and industrial machinery. 8,9 There are natural sources of infrasound such as ocean waves and volcanoes, as well as internal sources such as the heartbeat and respiration. A child playing on a swing experiences levels of infrasound of approximately 110 dB.…”
Section: Definitionsmentioning
confidence: 99%
“…3 Under good conditions with low wind speeds, the sound of wind turbines can appear benign or 'difficult to discern above the rustling of trees', as described by the British Wind Energy Association. 8 However, in suboptimal conditions the aerodynamic noise varies as the blades turn with changes in the strength and direction of wind. 3 Several studies have indicated that this amplitude modulated sound, rather than being a constant, steady type of noise, is more easily perceivable, and hence more likely to cause annoyance or health symptoms.…”
Section: 13mentioning
confidence: 99%
See 1 more Smart Citation